2021
DOI: 10.1002/arco.5245
|View full text |Cite
|
Sign up to set email alerts
|

Do Pleistocene rock paintings depict Sulawesi warty pigs (Sus celebensis) with a domestication character?

Abstract: The Indonesian island of Sulawesi harbours numerous early rock paintings of the endemic Sulawesi warty pig (Sus celebensis). Several S. celebensis images, including one dated to at least 45,500 years ago (ka), portray these suids with an anatomical character not observed in the living species: a pair of teat‐like protuberances in the neck area. This feature seems to be most consistent morphologically with neck “wattles”, cutaneous appendages only manifested in modern domestic swine (Sus scrofa) and some other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 107 publications
0
13
0
Order By: Relevance
“…The representational art of Indonesia is unrelated, and is nearly 7000 years earlier in Sulawesi and probably 3000 in Borneo (Aubert et al . 2018; 2019; Brumm, Oktaviana, Burhan et al 2021a, b). There has been very little discussion of the assumptions that would make comparison between Indonesia and Europe relevant to human evolution, though that is a crucial question.…”
Section: The Materiality Of Art Oral History and Gaps And Endingsmentioning
confidence: 98%
See 3 more Smart Citations
“…The representational art of Indonesia is unrelated, and is nearly 7000 years earlier in Sulawesi and probably 3000 in Borneo (Aubert et al . 2018; 2019; Brumm, Oktaviana, Burhan et al 2021a, b). There has been very little discussion of the assumptions that would make comparison between Indonesia and Europe relevant to human evolution, though that is a crucial question.…”
Section: The Materiality Of Art Oral History and Gaps And Endingsmentioning
confidence: 98%
“…Two conclusions follow from this: first, the original estimate was out by a matter of 10,000 years, as Clottes himself admits; second, the representational art at the site could be hailed as one of the earliest examples of cave art in France. The representational art of Indonesia is unrelated, and is nearly 7000 years earlier in Sulawesi and probably 3000 in Borneo (Aubert et al 2018;Brumm, Oktaviana, Burhan et al 2021a, b). There has been very little discussion of the assumptions that would make comparison between Indonesia and Europe relevant to human evolution, though that is a crucial question.…”
Section: The Materiality Of Art Oral History and Gaps And Endingsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, hypoplasias are not causally linked to domestication and the dental study does not rule out the possibility of alternative causes of LEH in this instance. Furthermore, a recent review of the painted "pig" figures found on the cave walls in the region has raised the possibility that a special and uniquely close relationship may have been established between hunter-gatherers and S. celebensis soon after initial human colonization of the island (Brumm et al 2021b).…”
Section: Leang Panninge Mallawa District Maros Regencymentioning
confidence: 99%